2017
DOI: 10.1007/s10792-017-0459-9
|View full text |Cite
|
Sign up to set email alerts
|

Changes in choroidal thickness in patients with diabetic retinopathy

Abstract: PurposeTo investigate the changes in choroidal thickness (ChT) following panretinal photocoagulation (PRP) for diabetic retinopathy (DR) and compare ChT in relation to DR severity.MethodsThirty-two eyes [19 eyes with proliferative DR (PDR) and 13 eyes with severe nonproliferative DR (NPDR)] for which PRP was necessary were analyzed. ChT was measured before PRP and at 1, 3, and 6 months after PRP using the swept-source optical coherence tomography. ChT of the 61 eyes matched with the PDR patients for the mean a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 27 publications
1
15
0
1
Order By: Relevance
“…However, the relationship between CT and DR severity is unclear (Table 6). Ohara et al [21] and Kim et al [25] found that the subfoveal CT (SFCT) of patients with mild to moderate NPDR was slightly lower than that of those with no DR, and the SFCT of patients with severe NPDR and PDR was greater than that of those with no DR. Ohara et al [21] found that the SFCT was greatest in those with severe NPDR, and the SFCT in the severe NPDR and PDR groups was significantly higher than that in the mild to moderate NPDR groups. Kim et al [25] found that the CT of the PDR group was the thickest, and was significantly higher than that of mild to moderate NPDR and severe NPDR groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the relationship between CT and DR severity is unclear (Table 6). Ohara et al [21] and Kim et al [25] found that the subfoveal CT (SFCT) of patients with mild to moderate NPDR was slightly lower than that of those with no DR, and the SFCT of patients with severe NPDR and PDR was greater than that of those with no DR. Ohara et al [21] found that the SFCT was greatest in those with severe NPDR, and the SFCT in the severe NPDR and PDR groups was significantly higher than that in the mild to moderate NPDR groups. Kim et al [25] found that the CT of the PDR group was the thickest, and was significantly higher than that of mild to moderate NPDR and severe NPDR groups.…”
Section: Discussionmentioning
confidence: 99%
“…Some clinical studies have explored the changes in CT in DM patients, with contradictory results, noting that the choroid became thinner [14][15][16][17][18], thicker [19], or showed no obvious changes [20]. Contrary results also appear in studies investigating DR and its influence on CT [15,19,[21][22][23][24][25]. It is worth noting that some studies have found that the CT of DM patients without DR was significantly decreased compared to that of control individuals, suggesting that choroidopathy may occur earlier than DR and may be a risk marker for the early stage of DR [15,26,27].…”
Section: Introductionmentioning
confidence: 99%
“…[14] Several studies have shown that the SFChT decreases after PRP and that PRP-treated eyes have a smaller SFChT than naïve eyes. [4,8,9,[15][16][17] Zhang et al found that the SFChT decreased significantly 3 months after PRP, [8] as did Okamoto et al, [9] while Ohara et al found that SFChT decreased significantly 6 months after PRP [17] and Kang et al reported a significant reduction in the SFChT 12 months after PRP. [15].…”
Section: Discussionmentioning
confidence: 99%
“…[14] Several studies have shown that the SFChT decreases after PRP and that PRP-treated eyes have a smaller SFChT than naïve eyes. [4,8,9,[15][16][17] Zhang et al found that the SFChT decreased significantly 3 months after PRP, [8] as did Okamoto et al, [9] while Ohara et al found that SFChT decreased significantly 6 months after PRP [17] and Kang et al reported a significant reduction in the SFChT in the 12 months after PRP. [15] Despite the consistent finding of a decrease in the SFChT during long-term observation, reports on the more short-term studies have been conflicting but suggest a significant increase in SFChT at 1-12 weeks after PRP.…”
Section: Discussionmentioning
confidence: 99%